Performance of weanling rabbits as affected by energy level and inclusion of biobiotics in the diet - El Hindawy M.; Yamani K.A.O.; Khashaba B.M.; Tawfeek M.I. (Rabbit production in hot climates, 1994)
A factorial design experiment was carried out (3x3) including three levels of dietary energy (2400, 2600 and 2800 DE kcal/kg feed) and inclusion of three groups. The first and second groups were supplemented with Lacto-Sacc and Bospro diets, respectively, while the third group was nonsupplemented as a control group. The basal diets were nearly isonitrogenous. A total of 126 purebred NZW rabbits were divided randomly into 9 treatment groups (equal in numbers and with insignificantly different live weights, at 5 weeks of age) and studied on growth response, digestibility and carcass traits during the period from 5 up to 12 weeks of age (marketing age). Results obtained could be summarized as follows: High level of energy was significantly (P less than 0.01 and P less than 0.05) the highest in values of live body weight, daily weight gain, feed conversion, nutrient digestibility coefficients, nutritive values (DCP, TDN and DE) and most of carcass traits as compared to the other levels of energy during the experimental period. The same trend was observed in viability (percentage) and performance index. Feeding rabbits with Lacto-Sacc or Bospro improved significantly (P less than 0.01 and P less than 0.05) live weight, daily weight gain, feed conversion, nutritive values (DCP, TDN, and DE) and most of carcass traits as compared to the control group. The same trend was observed in performance index and economical efficiency. High dietary energy level, inclusion of either Lacto-Sacc or Bospro to the diet and the interaction between high dietary energy level and the biobiotics inclusion to weanling rabbit diet improved significantly (P less than 0.01 and P less than 0.05) most growth performance traits and were of favourable effect on most of the nutritional parameters, digestibility of nutrients and all carcass traits except giblets (percentage). The performance index and economic value for both the high dietary energy level and the inclusion of biobiotics were pronounced.
1. International Conference of rabbit production in hot climates, 1994/09/06-08, Cairo (Egypt)